2015
DOI: 10.1002/anie.201509218
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,1‐Diborylalkenes through a Brønsted Base Catalyzed Reaction between Terminal Alkynes and Bis(pinacolato)diboron

Abstract: Abstract:A new method for the synthesis of 1,1-diborylalkenes through a Brønsted-base-catalyzed reaction between terminal alkynes and bis(pinacolato)diboron has been developed. The protocol allows direct synthesis of functionalized 1,1-diborylalkenes from various terminal alkynes including propiolates, propiolamides and 2-ethynylazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 33 publications
3
53
0
1
Order By: Relevance
“…In 2015, Sawamura and co-workers reported the direct preparation of 1,1-diborylalkenes from terminal alkynes and B 2 Pin 2 using LiO t -Bu as the catalyst (Scheme 2A). 13 While effective and an important advance, this reaction is limited to alkynes bearing electron-withdrawing substituents such as propiolates.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Sawamura and co-workers reported the direct preparation of 1,1-diborylalkenes from terminal alkynes and B 2 Pin 2 using LiO t -Bu as the catalyst (Scheme 2A). 13 While effective and an important advance, this reaction is limited to alkynes bearing electron-withdrawing substituents such as propiolates.…”
Section: Introductionmentioning
confidence: 99%
“…[2a, 15] The first metalcatalyzed diboration of alkynes was reported by Suzuki and Miyaura in 1993 using a Pt catalyst, [16] and significantly improved Pt catalyst systems were reported by our group. [17] During the last few years, Pd, [18] Cu, [19] Co, [11c, 20] Fe, [21] Zn, [14x] and metal-free [22] systems were reported for the diboration of alkynes, which provide practical and economic alternatives to the Pt-catalyzed processes (Scheme 2 b). [16][17]23] However, the availability of diverse multiborylalkenes is quite limited because of the lack of efficient and versatile synthetic methods.…”
mentioning
confidence: 99%
“…In 2015 Ohmiya and Sawamura reported the 1,1‐diboration of triple carbon–carbon bonds with B 2 pin 2 . Activated terminal alkynes were selected to probe this new concept, including those containing a propiolate, a propiolamide or a imidazole substituent (Scheme a–c).…”
Section: Synthesis Of 11‐diborylalkenesmentioning
confidence: 99%
“…This is the case in Suzuki–Miyaura coupling between the β,β‐diborylacrylate shown in Scheme and bromobenzene in the presence of a Pd(OAc) 2 catalyst precursor modified with DtBPF [DtBPF = 1,1′‐bis(di‐ tert ‐butylphosphanyl)ferrocene] and K 3 PO 4 as a base. Sawamura and co‐workers demonstrated that the cross‐coupling occurs selectively at the boron site trans to the ester group to give the corresponding alkenylboronate (with E/Z > 99:1) in high yield (Scheme ) . This stereoselectivity is probably due to the steric character of the ester group.…”
Section: Reactivity Of 11‐diborylalkenesmentioning
confidence: 99%
See 1 more Smart Citation